PENGARUH TANGIBLE DAN FASILITAS TERHADAP KEPUASAN PENGUNJUNG PADA WISATA RELIGI WALISONGO DI PULAU JAWA - Syahputra, Hendra (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
Wali Songo is the nine historic figures who participated in the spread of Islamic teachings on the island of Java. The guardians not only spread the religion of Islam alone, but also actively build progress for the local community through the field of reading and writing education, cultural arts, and the planting of wisdom that comes from the teachings of Islam. The tomb of the Wali Songo is now used as a religious tourism activity through the grave pilgrimage activities. Almost every tomb that there Wali Songo always crowded by people from around the archipelago. The purpose of this research is to know: 1) tangible influence to satisfaction of tourist tourism of walisongo religion, 2) influence of facility to satisfaction of tourist visit of walisongo religion, 3) tangible influence and facility simultaneously to the satisfaction of religious tourism visitor walisongo. This type of research is a quantitative research with a population of tourists visiting religius tourism walisongo. The number of samples in this study amounted to 45 samples. Data analysis technique used multiple regression analysis with SPSS program.